Fotografia i film w praktyce artystycznej oraz propozycjach teoretycznych Davida Hockneya - Zawojski, Piotr (Artium Quaestiones, 2020)
In his diverse works, David Hockney has used, and still uses, various media, which in some periods of his activity gained leading significance, while in the following they were abandoned or temporarily abandoned. But no matter what medium in the given period was the main form of creativity, the focus of his interest has always been the issue of image and imaging. The article is devoted to the practice and theoretical recognition of photography, which was a kind of introduction to experiments with a moving image. The author refers to the artist's numerous publications on the theory and history of image and imaging (including Secret Knowledge, History of Images, On Photography). Photography led to Hockney's audiovisual realizations. This is a kind of repetition of the natural evolution and developmental progression of the media, also, and perhaps above all, in the technological dimension. The article is divided into three parts. In the first part, the author presents Hockney as a practitioner and theoretician, in whose activities both these activities are closely intertwined. This is a sign of the times: practice and theory are equally important, awareness of the medium, or artistic and aesthetic self-awareness of artists, is an expression of the spirit of the era in which an intuitive approach to art today seems inefficient, not to say impossible. Hockney appears to be an exemplary artist, who is extremely conceptual in his artistic practice as a consequence of his research on the history of art and a constantly developed set of his own theoretical findings. He is an artist discursively commenting not only on his work as an artist in many media (painting, drawing, graphics, set design, photography, film, computer graphics), but also an art and media theoretician reflecting on the fate of images in a changing media landscape. The second part of the article is devoted to the reconstruction of Hockney's theoretical reflections on photography and the analysis of his photographic projects. First of all, experimental Polaroid compositions created in the early eighties, named by the artist joiners, as well as photographic collages and photographic images realized in the later periods of the British artist's work. The third part considers digital movies, as Hockney calls them, audiovisual realizations referring to both his previous photographic works and experimental video films in which multi-camera systems are used.